KLASIFIKASI TINGKAT KEKERINGAN PADA DAERAH ALIRAN SUNGAI (DAS) LIMBOTO (Classification Of Drought Level In Limboto Watershed) - Sri Rahayu Ayuba; Munajat Nursaputra; Tisen Tisen (Jurnal Sains Informasi Geografi, 2018)
Abstract - Changes in land use are the socio-economic forces that most encourage changes and ecosystem degradation. Disruption of the hydrological cycle has caused "3 T" classic problems of water "too much (which causes flooding)," too little (which causes drought) and "too dirty (which causes water pollution). Based on data from BNPB in 1979-2009 there were 8 drought events in Gorontalo Province. This research was carried out in the Limboto Watershed with an area of 86412.6 ha. The method used is the SWAT Method (Soil and Water Assessment Tool) using ArcSwat software that integrates GIS. This research is included in non-experimental research that is by using direct observation in the field. Input of SWAT data include slope, land cover type, climate, and soil type. The analysis used in determining the vulnerability of the watershed to drought is to use the Soil Moisture Deficit Index (SMDI) through the Soil Water (SW) parameter. In this study the use of SWAT model output through ArcSwat, has been able to describe the condition of water supply in the Limboto watershed, which as a whole has been included in the "Vulnerable" category. By comparing the area that experienced drought before and after simulation / running land use directives, it can be concluded that the difference in the area of the watershed that experiences drought with the "Vulnerable" classification is obtained 37,513.1 ha or a decrease of 43.4% from watershed area. Keywords: Drought, Direction for Land Use, Limboto River Basin, Landing Simulation Abstrak – Perubahan penggunaan lahan merupakan kekuatan sosial ekonomi yang paling mendorong perubahan dan degradasi ekosistem. Terganggunya siklus hidrologi telah menimbulkan “3 T” masalah klasik air “too much (yang menimbulkan banjir), “too little (yang menimbulkan kekeringan) dan “too dirty (yang menimbulkan pencemaran air). Berdasarkan data BNPB tahun 1979-2009 terdapat 8 kejadian kekeringan di Provinsi Gorontalo. Penelitian ini dilaksanakan pada Daerah Aliran Sungai (DAS) Limboto dengan luas DAS 86412,6 ha. Metode yang digunakan adalah Metode SWAT (Soil and Water Assessment Tool) dengan menggunakan software ArcSwat yang terintegrasi SIG. Penelitian ini termasuk dalam penellitian non-eksperimen yakni dengan menggunakan pengamatan langsung di lapangan. Input data SWAT antara lain lereng, jenis tutupan lahan, iklim, dan jenis tanah. Analisis yang digunakan dalam menentukan kerentanan DAS terhadap kekeringan adalah dengan menggunakan Soil Moisture Deficit Index (SMDI) melalui parameter Soil Water (SW). Pada penelitian ini penggunaan output model SWAT melalui ArcSwat, telah mampu menggambarkan kondisi pasokan air pada DAS Limboto, yang secara keseluruhan telah termasuk dalam kategori “Rentan”. Dengan membandingkan luas area yang mengalami kekeringan pada sebelum dan setelah dilakukan simulasi/running arahan penggunaan lahan maka dapat disimpulkan bahwa selisih luas area DAS yang mengalami kekeringan dengan klasifikasi “Rentan” diperoleh 37.513,1 ha atau secara persentasi mengalami penurunan sebesar 43,4 % dari luas DAS. Kata Kunci: Kekeringan, Arahan Penggunaan Lahan, Daerah Aliran Sungai Limboto, Simulasi Arahan